Dakwah Kultural, Karya Ulama Indonesia Kajian Untuk Menangkal Radikalisme Agama - Wajdi, Muh. Barid Nizaruddin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2016)
It is undeniable that some Indonesian Muslims comprehend Islam in radicalism perspective. They use several ways to spread this radicalism through the organization of cadres, speech in mosques that managed under their control, magazines publishing, booklet and books, and through various websites on internet. Although many people develop tendentious speculation that terrorism originates from fundamentalism and religious radicalism, but not a few who believe that the motives of radicalism and terrorism are not sourced from a single aspect. This article discusses about the propaganda (Dakwah) that is carried out by Muhammad (pbuh), Walisongo and theologian (Ã¢â¬ËUlama). The term of dakwah is often used by Muslims who spread theirbeliefs to others There are some Muslims who engage in dakwah actively. This clearly requires a preacher to adapt the method used, especially in modern era. Such as, the first is dakwah bil kitabah, the method of dakwah by writing, either through books, newspapers or magazines. The second is dakwah bil lisan. Dakwah verbally (linguistic) such as, seminar, symposium, discussion, sermon, opened discussion, chatting etc. The third is dakwah bi al-hal. Dakwah with the act, which is expressed in action to the development of the surrounding environment.